Processing pulp fiber into high strength composites. Issue 7 (3rd July 2022) - Wang, Shiming; He, Susu; Zhang, Weifeng; Wen, Aishi; Olonisakin, Kehinde; Zhang, Xinxiang; Ran, Li; Wenbin, Yang
ABSTRACT: The mechanical performance of wood fibre-based panels is unsatisfactory for many advanced engineering structures and applications; it also releases free formaldehyde. Here, we report a simple and effective strategy to transform wood fiber (pulp fiber) into high strength composite panels without adhesive bonding. Our two-step process involves layer by layer self-assembly of bleached cellulose mixed with microcrystalline cellulose (MCC) and dibasic calcium phosphate (DCP). This was followed by hot-pressing, leading to the complete densification of the wood pulp fiber with highly aligned cellulose nanofibers. The result showed that the flexural and tensile strength could reach up to 147MPa and 58 MPa, respectively, which are much stronger than those of existing types of wood fiberboard, mainly resulting from the synergistic effects of hydrogen bonding and ionic bonding between the pulp fibers and DCP sheets. Graphical abstract: uf0001